Cube Satellite Project (KN-Sat1) (University of Khartoum Engineering Journal, 2022)
Cube Satellites are small-sized satellites (Nano-Satellites) meant for educational and research purposes. A new vision of brining huge space programs into universities and institutes, and involving undergraduates and postgraduates in such practical projects while they are receiving the theoretical aspects behind designing, integrating, testing and launching the satellites. This practical knowledge will lead to advancement and in pioneering in Sudan’s future space programs.